THE PRINCIPAL'S LEADERSHIP STYLE IN IMPROVING TEACHER PERFORMANCE AT SMPN 1 DARUL IMARAH ACEH BESAR - Rusydi; Muhammad Iqbal; Rahmattullah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Teacher performance is an important factor in determining the success of the educational process. However, various problems such as low discipline, lack of work motivation, and weak mastery of learning strategies continue to be challenges within the school environment. In this context, the principal has a strategic role as an educational leader who is capable of improving teacher professionalism and performance through the implementation of effective leadership styles. This study aims to analyze the principal’s leadership style in improving teacher performance, teacher work discipline, and the obstacles encountered in efforts to enhance teacher performance at SMPN 1 Darul Imarah. The research employs a qualitative approach with a descriptive method. Data were collected through observations, in-depth interviews, and documentation studies involving the principal, vice principal, and teachers as research participants. The findings indicate that the principal applies a combined and adaptive leadership style that integrates transformational, transactional, visionary, and situational approaches. The transformational style is reflected through motivation, coaching, and exemplary behavior. The transactional style is implemented through the enforcement of rules, rewards, and sanctions. The visionary style is demonstrated through the communication of the school’s vision and the involvement of teachers in achieving organizational goals. Meanwhile, the situational style is applied by adjusting leadership approaches to the conditions and characteristics of teachers. The implementation of these various leadership styles has created a collaborative and conducive work environment that is oriented toward improving the quality of education. The obstacles encountered include limited facilities and infrastructure, low discipline among some teachers, and insufficient mastery of learning strategies. To address these challenges, the principal conducts coaching, training, supervision, and the provision of supporting facilities. The study concludes that the principal’s leadership style plays a significant role in improving teacher performance and enhancing the effectiveness of the learning process.